Retail Analytics-An Attempt to Understand Customers and Predict - Dr. Kalim Khan, Prof. Mohd. Osaid Koti (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the modern era of business competition, prediction of customer psychology and his behavior as per the changing market rivalry are very important. The present paper explores the importance of Retail analytics to predict customer behavior. In Retail marketing prediction of customer behavior is very important. This papers explores customer behavior insights, Humanizing selling and Return on Investments, In store operations, managing basics, Enhancing loyalty are very important in Retail analytics. Hence the present study found that there is a positive relationship between the customer purchasing patter and considered variables.